2018
DOI: 10.2174/1871520617666170719155517
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of IRE1α Associates with the Resistant Mechanism of Osimertinib (AZD9291)-resistant non-small Cell Lung Cancer HCC827/OSIR Cells

Abstract: An increased expression of IRE1α may be one of the resistant mechanisms for OSI-resistant NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Osimertinib for second-line treatment in EGFR T790M positive NSCLC was associated with a response rate of 61% and PFS of 9.6 months [ 13 ]. But the mechanism of osimertinib resistance is much complicated [ 6 , 7 ]. Third-generation EGFR-TKIs (WZ 4002, rociletinib, osimertinib) have pyrimidine structure and covalent bond with EGFR Cys797 at ATP binding pocket.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osimertinib for second-line treatment in EGFR T790M positive NSCLC was associated with a response rate of 61% and PFS of 9.6 months [ 13 ]. But the mechanism of osimertinib resistance is much complicated [ 6 , 7 ]. Third-generation EGFR-TKIs (WZ 4002, rociletinib, osimertinib) have pyrimidine structure and covalent bond with EGFR Cys797 at ATP binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotype transformation, EGFR new point mutation, pathways activation, or targets loss were the strongest possibilities. Most studies reported that C797S mutation happened in 20–30% of patients after osimertinib initiation [ 6 , 7 ]. The EGFR C797S mutation conferred resistance to third-generation EGFR-TKI.…”
Section: Introductionmentioning
confidence: 99%
“…26 ERN2 also activates serine/threonine-protein kinase and participates in the response to EGFR-TKIs. 27,28 Our study observed that the expression of EEF1A2 was downregulated in patients with MLNM harboring EGFR 19Del mutations compared with those patients without MLNM, and conversely upregulated in patients with MLNM harboring EGFR L858R mutations, whereas the expression of ERN2 was upregulated in patients with EGFR 19Del mutations and downregulated in those with EGFR L858R mutations. The expression of ERN2 was verified with quantitative RT-PCR in these 10 patients and found to be consistent with the results from transcriptome sequencing.…”
Section: Discussionmentioning
confidence: 64%
“…TGF-β1 activates ERK signaling, which is required for TGF-β1-mediated EMT in vitro 63 67 . However, IRE1α overexpression was associated with the resistant mechanism to osimertinib in NSCLC HCC827/OSIR Cells 68 . Similarly, several studies have shown that IRE1α plays a contradictory role in colon cancer cells [69][70][71][72] .…”
Section: Discussionmentioning
confidence: 92%